Idiopathic Intracranial Hypertension Triggering Hemifacial Spasm. Issue 2 (June 2021) - Garcia, Maria D.; Mansukhani, Sasha A.; Chen, John J.; Bhatti, M. Tariq
Abstract : Abstract: Idiopathic intracranial hypertension (IIH) is a syndrome associated with increased intracranial pressure without a clear underlying cause that is classically seen in young women. Patients typically present with headache and ocular findings, including disc edema and, less frequently, an abduction deficit. To make a diagnosis of IIH, other than cranial nerve 6 or 7 dysfunction, patients must have a normal neurologic examination. When cranial nerve 7 is affected patients can present with hemifacial spasm. We present the case of a young woman with IIH who had hemifacial spasm as one of the presenting symptoms. Her symptoms resolved once she was treated for IIH with acetazolamide. Abstract : Supplemental Digital Content is Available in the Text.